Ratio Decidendi of Supreme Court Decision No. 23 P/HUM/2024 on Judicial Review of Age Requirements for Candidates for Governor - Yensi Prasilia; Rustan, Ahmad; Nashriani Jufri, Nur; Malie, Adi Muliawansyah (Journal of Law, Politic and Humanities, 2025)
Regional elections are a means of exercising popular sovereignty that allows citizens to directly elect leaders at the regional level while providing legitimacy to democratically elected governments. In their journey, political elites often use various methods to become contestants or to prevent their political opponents from competing by changing various legal rules that are considered ‘obstructing’ their political goals through judicial review (JR) at the Supreme Court against regulations under the law. This study aims to analyse the ratio decidendi of Supreme Court Decision No. 23 P/HUM/2024 which changes the age requirement for nominating regional head candidates from the age when they are determined as candidates by the KPU to the inauguration requirement. This research is a type of legal research using 2 (two) types of legal approaches, namely statute approach and conceptual approach. The results showed that the ratio decidendi in the case considered the importance of providing opportunities for the younger generation to participate in the political process and the human rights aspect that age restrictions can be considered a violation of individual political rights.This consideration is a real mistake considering that the position of the judge in deciding JR cases at the Supreme Court acts as a Negative Legislator who is limited to making an assessment of whether the regulation that is the object of the test is contrary to the law as the touchstone?Textually, the KPU regulation that is the object of the test is still in line with the Law so that the petition should be rejected.